THE ROLE OF THE MEANS OF COMMUNICATION IN SHAPING THE TRENDS OF THE IRAQI PUBLIC TOWARDS THE ELECTION CAMPAIGNS OF THE US PRESIDENTIAL CANDIDATES 2020 - Prof. Dr. Mohamed Hassan Al- Amri/, Ali Sadiq Al- Saadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The tremendous and continuous development of communication technology in the modern era has been reflected in the increase in the influential power of the media and its increasing danger. It has played a major role in the formation of the individual’s perception of the world around him, and in his formation of facts, opinions and beliefs about this world, which led to communication taking an international character. And it is heading towards globalization, which has become prevalent in all human activities, and the integration between traditional and digital media has increased, and exposure to the means of communication has become part of the fabric of the daily life of the public, and these Changes in the field of communication have had great effects in our societies, coinciding with the growing influence of the means of communication, which has become the most important basic sources. To obtain information, and as a result of the great interest of these media locally,Arably and internationally in the electoral campaigns of the US presidential candidates in 2020, they played a role in shaping the knowledge, concepts and political trends of the public and it became difficult to challenge or deny them, as the issue of electoral campaigns became a major Concern to know the results of those election campaigns, especially the means of communication exercise a clear influence on public opinion in this field By shaping the audience’s trends and building their perceptions of personalities and events that they do not have direct contact with, and whose role goes beyond merely presenting reality to putting it in a framework, and dealing with it with analysis, interpretation and explanation. Given the need of the Iraqi public, with their different segments, to know what is happening in the world around them in terms of political events and issues, this study sought to identify the extent to which the Iraqi public relied on the means of communication in following up on one of the most important political events that took place in 2020, which is the electoral campaigns of the US presidential candidates, which is associated with the great influence power and the only pole of the world now, and its interest in it extended to the whole world, especially the Arab and local, especially we in Iraq affected by the results of those election campaigns as a result of the US political interventions locally and regionally for the Iraqi individual, that this study will depend on the approach of relying on the media, The basic idea of ??this approach is crystallized in that the recipient within modern societies depends on the media as sources of information that contribute to the for mation of his knowledge and orientations about what is happening in the community or other societies, where individuals obtain an enormous amount of information through the media that makes them more understanding and less anxious, as well as It helps them in directing their behavior and making their decisions. The changes that have affected the life of the modern person have made him very interested in what he should do It also imposed new patterns and more efficient methods of obtaining information, making the means of communication the main source of information on current events.